50.9k views
2 votes
Rewrite without parentheses and simplify.
(5x+6v)^ 2?

2 Answers

3 votes

answer: 36v^2 +60vx +25x^2

User Mjdth
by
5.0k points
4 votes

Expand:

(5x + 6v)² = (5x + 6v)(5x + 6v)

Remember to follow FOIL:

FOIL is the order in which to multiply when multiplying terms with differing variables:


(5x + 6v)(5x + 6v)

First:
(5x)(5x) = 25x^(2)

Outside:
(5x)(6v) = 30xv

Inside:
(6v)(5x) = 30xv

Last:
(6v)(6v) = 36v^(2)

Combine like terms:


25x^(2) + 30xv + 30xv + 36v^(2) \\= 25x^(2) + (30xv + 30xv) + 36v^(2)\\= 25x^(2) + 60xv + 36v^(2)

Remember to order in descending power (if your teacher asks for it):


25x^(2) + 36v^(2) + 60xv

~

User Fukudama
by
5.0k points